Draft Genome Sequence of Lactobacillus plantarum wikim18, Isolated from Korean Kimchi - Jang, Ja Young (American Society for Microbiology, 2014)
This report describes the draft genome sequence of Lactobacillus plantarum strain wikim18, isolated from the traditional Korean food kimchi. The reads generated by Ion Torrent PGM were assembled into 327 contigs. RAST annotation of the genome revealed 12 tRNAs and 3,316 protein-coding gene sequences.